Penyuluhan Manfaat Multivitamin untuk Imunitas Tubuh di Masa Pancaroba - Endriyatno, Nur Cholis; Ningrum, Dian Ayu; Hafidzah, Eni; Ramadani, Noveria Riski; Cahyaningtiyas, Nur; Widiawati, Rahma (Jurnal Pengabdian Masyarakat Bhinneka, 2022)
The immune system is an essential thing and needs to be maintained, this is done so that the body's immune system remains in a strong and optimal condition. A body with a good and strong immune system is very important and has a vital role in the body's defense, especially in terms of preventing various diseases, especially infectious ones, especially during the transition season. Some of the people in the Pandanarum Tirto sub-district are known to be less concerned about health, especially in maintaining their immune system. From this background, educational activities were carried out to increase public understanding in the blood about the importance of the role of multivitamins in the transition season. Education is carried out by delivering material and question and answer discussions. This community service activity is in the form of counseling with the aim of helping the community to change their lifestyle/behavior and be aware of the importance of consuming multivitamins for immunity in the transition season. With this activity, it is hoped that the public can understand the importance of taking multivitamins in the transition season and can also find out information on how to use multivitamins properly and appropriately to obtain and maximize therapy. The conclusion of this service activity is that the community becomes more aware, understands, and is interested in the importance of the benefits of multivitamins for body immunity in the transition season.